Combined FCGR2A (131H/R) and FCGR3A (158F/V) genotypes and their gender-specific association with chronic and refractory immune thrombocytopenia in Palestinian children - Amer, Khitam; Amer, Johnny; Taha, Adham Abu; Baker, Wisam; Abuhamed, Awad; Salhab, Ahmad (Frontiers in Medicine, 2025)
BackgroundImmune thrombocytopenia (ITP) is a common pediatric autoimmune disorder characterized by low platelet counts and heightened bleeding risk. Fc gamma receptors (FcγRs), particularly FCGR2A (131H/R) and FCGR3A (158F/V), mediate immune responses and may influence ITP susceptibility and progression. Gender-related genetic variation has been proposed but remains underexplored, particularly in Middle Eastern pediatric populations. This study aimed to perform an exploratory assessment of the prevalence and potential clinical relevance of FCGR2A and FCGR3A polymorphisms, including gender-based tendencies, in Palestinian children with ITP.MethodsA multicenter case-control study included 40 proven pediatric ITP patients (20 males, 20 females; mean age 6.76 ± 4.13 years) and 80 age- and sex-matched healthy controls. Genotyping was performed using PCR-RFLP and nested PCR. Genotype frequencies were correlated with disease phenotype and sex.ResultsNo statistically significant differences in genotype distributions were observed between ITP cases and controls for either FCGR2A (HH: 17.5%, HR: 62.5%, RR: 20.0%) or FCGR3A (FF: 25.0%, FV: 55.0%, VV: 20.0%) (p > 0.05). However, a secondary, exploratory analysis for gender-specific trends yielded noteworthy observations: FCGR2A-HH was numerically more frequent in male ITP patients (57.4%) than in females (42.8%), while HR was lower in males (48% vs. 52%). Similarly, FCGR3A-VV occurred in 62.5% of male ITP patients versus 37.5% in females. Furthermore, the combined HR/FV genotype (32.5%) showed a non-significant trend of association with chronic ITP (69.2%), while the VV/HH genotype, although rare (5%), was linked to 50% of refractory presentations.ConclusionThis exploratory study found no statistically significant association between FCGR2A and FCGR3A polymorphisms and overall ITP susceptibility in the full cohort. However, the observed trends, particularly the distinct gender-based distribution of specific genotypes and the association of combined genotypes with chronic and refractory disease, suggest that these genetic markers may play a role in disease progression. Further investigation in a larger, appropriately powered study is warranted to validate these findings and to understand their potential to guide personalized treatment approaches for pediatric ITP.